2019
DOI: 10.4025/actasciagron.v41i1.42631
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-physiology, yield, and water-use efficiency of<i>Opuntia ficus-indica</i> irrigated with saline water

Abstract: Forage cactus pear is considered a xerophilic plant, so it is adapted to harsh semiarid conditions and is a forage resource of significant importance for animal production in regions that are subject to food shortage and long dry periods. We aimed to evaluate the morphometric and physiologic characteristics and water-use efficiency of ‘Gigante’ forage cactus pear under different settings of irrigation depth and irrigation intervals with saline water. The treatments included seven conditions of water applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
4
20
0
8
Order By: Relevance
“…Irrigation for forage cactus crops in the irrigated perimeter of Ceraíma and in the Valley of Iuiu (Table 2) has contributed to increase their yield (FONSECA et al, 2019) to values higher than those found for agroecosystems with low fertility soils and water deficit, such as Riacho de Santana (Table 1). Forage cactus crops in Riacho de Santana had the lowest yield, with a mean of 15 Mg ha -1 year -1 ( Table 6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Irrigation for forage cactus crops in the irrigated perimeter of Ceraíma and in the Valley of Iuiu (Table 2) has contributed to increase their yield (FONSECA et al, 2019) to values higher than those found for agroecosystems with low fertility soils and water deficit, such as Riacho de Santana (Table 1). Forage cactus crops in Riacho de Santana had the lowest yield, with a mean of 15 Mg ha -1 year -1 ( Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…The structural characteristics of four randomized plants in each of the three replications (12 plants) of each of the 20 properties were evaluated, totaling 240 plants (GUIMARÃES et al, 2019). These characteristics consisted of: cladode thickness (CT), determined in the middle part of all cladodes; cladode width (CW), measured in the highest widest part of the cladode; cladode length (CL), measured in the longest part of the cladode; total number of cladodes (TNC) per plant; plant height (PH), distance from the top of the highest cladode and the soil; cladode area (CA) [CA (cm 2 ) = CC x LC x 0.693); 0.693 is the correction factor due to the elliptical form of the cladode (PINTO et al, 2002)]; total cladode area (TCA); cladode area index (CAI), which is the TCA of both sides of the cladodes divided by the area used by the plant (AUP) (m 2 of cladode per m 2 of soil).…”
Section: Evaluation Of Plant Structural Characteristics and Yieldmentioning
confidence: 99%
“…According to Fonseca et al (2019), an important physiological characteristic is the cladode area index, since the higher the CAI is, the larger the area for the absorption of photosynthetically active radiation and, consequently, the greater the crop yield. Among the factors that affect the CAI, the nutritional status of the plant stands out.…”
Section: Cladode Area Index (Cai)mentioning
confidence: 99%
“…Apesar desta boa adaptabilidade no semiárido do nordeste, alguns estudos vêm mostrando que quando a precipitação pluvial local não atinge os níveis considerados ideais, faz-se necessário o uso de irrigação suplementar para atender as necessidades hídricas da palma forrageira, sendo uma ótima opção para incrementar o rendimento da cultura, onde promove melhorias em características relacionadas à sua produtividade, como crescimento da planta, número de cladódios e índice de área do cladódio (Queiroz et al, 2015;Amorim et al, 2017;Barbosa et al, 2017a;Cruz Neto et al, 2017;Silva et al, 2017a;Lima et al, 2018b;Fonseca et al, 2019).…”
Section: Introductionunclassified
“…Na literatura existem diversos trabalhos que mediram o efeito da irrigação suplementar na produtividade, na ET e/ou na EUA de palma forrageira (Barbosa et al, 2017b;Cruz Neto et al, 2017;Morais et al, 2017;Pereira et al, 2017;Fonseca et al, 2019), contudo todas essas pesquisas foram realizadas em região de clima semiárido, com condições mais secas e quentes que a região agreste ou que os brejos de altitude de Pernambuco.…”
Section: Introductionunclassified